The moderating role of sexual minority status in the associations of the experience and tolerance of shame‐related emotions to suicide risk. Issue 12 (4th May 2022) - Mann, Adam J. D.; Kurtz, Andrew J.; Tull, Matthew T.; Gratz, Kim L.
Abstract: Objective: This study examined the associations of the experience and tolerance of shame‐related emotions to suicide risk, as well as the moderating role of sexual minority status. Methods: Community adults ( N = 360) were recruited via MTurk and completed self‐report questionnaires. Hierarchical regression analyses examined the main and interactive associations of sexual minority status and shame‐related variables to suicide risk. Results: Results revealed significant positive associations between self‐disgust and suicide risk for sexual minority and heterosexual participants, although the magnitude was greater for sexual minority participants. Additionally, tolerance of shame was significantly negatively related to suicide risk only among sexual minority participants. Finally, exploratory analyses examining the three‐way interaction of self‐disgust, shame tolerance, and sexual minority status revealed a significant negative association between shame tolerance and suicide risk only among sexual minority participants with high levels of self‐disgust. Conclusion: Results highlight the relevance of shame‐related experiences to suicide risk among sexual minorities.